THE IMPORTANCE OF GASTRIN IN THE DIGESTION PROCESS - Ahmadaliyev Shokhruk Shukhratovich; Numonova Sayyora Salimjan daughter (European Science Publishing, 2024)
Gastrin is a hormone produced by the G cells of the stomach, pancreas, and duodenum. Participates in the regulation of digestion. Gastrin production is activated by reducing the acidity of the stomach, stretching the walls of the stomach, and eating a lot of protein foods. Gastrin affects the parietal cells of the gastric mucosa, which are responsible for the production of hydrochloric acid. It also affects the movement of bile, pancreatic secretion and gastrointestinal tract. Normally, when food is consumed, there should be an increase in the production of hydrochloric acid and a decrease in its level after digestion. Increased levels of hydrochloric acid decrease gastrin production through a feedback mechanism.
Keywords: gastrin, Zollinger-Ellison syndrome, Addison-Birmer syndrome, vitamin B12.Relevance of the topic.